PRAKTIK MEMBACA DAN MENULIS AL-QUR’AN UNTUK MENGURANGI PERILAKU NEGATIF SISWA DI SEKOLAH MENENGAH KEJURUAN (SMK) - Dody Riswanto; Syifa Jauhar Nafisah (QATHRUNÂ, 2025)
This study aims to examine the practices of reading and writing the Qur'an in reducing negative behaviors among students in Vocational High Schools (SMK). The study seeks to analyze how the practices of reading and writing the Qur'an contribute to reducing negative behaviors of SMK students. Negative behaviors in SMK students, such as violations of rules, attendance issues, tardiness, bullying among students, school fights, and other tendencies toward aggressive behavior, remain serious challenges in the educational field. One approach used by value-based religious schools is the implementation of reading and writing the Qur'an as part of student character development. This study uses a qualitative approach with data collection techniques, including observation, document study, and audiovisual information. The results of the study indicate that the practice of reading and writing the Qur’an regularly and in a structured manner can reduce negative behavior in students. In general, some students still repeat negative behaviors after being given interventions in reading and writing the Qur’an, along with additional interventions such as written statements, cleaning school corridors, and performing the five daily prayers with photo evidence including the date, time, and location, but with significantly reduced intensity. This becomes an important note for guidance and counseling in schools, that completely stopping students' negative behavior is very difficult, but counselors can reduce or diminish the intensity of students' negative actions to a lower level. This study emphasizes that religious activities can be used as a fairly effective character education strategy in vocational schools.